2010
DOI: 10.1021/jf904279j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage and Cooking on β-Carotene Isomers in Carrots (Daucus carota L. cv. ‘Stefano’)

Abstract: Carrots are one of the highest dietary sources of beta-carotene and are naturally high in the (all-E)-beta-carotene isomer, which has higher bioavailability, provitamin A activity, and antioxidant capacity compared to Z (cis) isomers. The objectives of the present study were to investigate the effects of storage temperature, time, and cooking (boiling for 15 min) on the levels of carotene isomers in 'Stefano' carrots. Storing carrots at either 4 degrees C to simulate long-term storage or 20 degrees C to simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 34 publications
2
46
0
1
Order By: Relevance
“…In our study for a given type of pouch, the temperature effect was significantly ( p < 0.05) higher at 13 °C than for the other two temperatures. This may be attributed to more efficient extraction of carotene after storage due to cell wall softening and membrane destabilization (Imsic, Winkler, Tomkins, & Jones, ). Imsic et al () reported a 25 and 34% increase in all‐trans‐β‐carotene in raw carrots stored at 4 and 20 °C, respectively, followed by a gradual reduction to level similar to the initial value.…”
Section: Resultsmentioning
confidence: 99%
“…In our study for a given type of pouch, the temperature effect was significantly ( p < 0.05) higher at 13 °C than for the other two temperatures. This may be attributed to more efficient extraction of carotene after storage due to cell wall softening and membrane destabilization (Imsic, Winkler, Tomkins, & Jones, ). Imsic et al () reported a 25 and 34% increase in all‐trans‐β‐carotene in raw carrots stored at 4 and 20 °C, respectively, followed by a gradual reduction to level similar to the initial value.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation of the higher content of β-carotene after boiling treatment could be the formation of Z (cis) isomers generated during the cooking from the degradation of the all-trans isomers. Recently, Imsic, Winkler, Tomkins, and Jones (2010) have observed that the cooking of carrots has produced (15 Z)-β-carotene isomers, a fact which was not observed in raw carrots. This isomerization occurs when the temperature employed is high enough to induce the dissolution of the crystal structure of the β-carotene (Imsic et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Imsic, Winkler, Tomkins, and Jones (2010) have observed that the cooking of carrots has produced (15 Z)-β-carotene isomers, a fact which was not observed in raw carrots. This isomerization occurs when the temperature employed is high enough to induce the dissolution of the crystal structure of the β-carotene (Imsic et al, 2010). It is well reported that after boiling, β-carotene content shows an increase (Azizah, Wee, Azizah, & Azizah, 2009;Bernhardt & Schlich, 2006;Hwang & Kim, 2013;Kidmose, Christensen, Agili, & Thilsted, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…After the thermal treatments, 13-Z-β-carotene was formed in the highest amount, followed by 15-Z-and 9-Z-β-carotene, except for the treatment at 130°C, at which 9-Z-β-carotene became more important than 15-Z-β-carotene after long treatment times. Similarly, Imsic et al 25 found that 13-Z-β-carotene was predominantly formed in carrots after boiling for 15 min, followed by 15-Z-β-carotene and with 9-Z-β-carotene being the least abundant isomer. After 60 min at 85°C, 67.9% of all Z-isomers in the oil/carrot emulsion was present as 13-Z-β-carotene, whereas 15-Z-β-carotene accounted for 32.1% of the total Z concentration and 9-Z-β-carotene was still not formed.…”
Section: ■ Introductionmentioning
confidence: 83%